Spiritual Degeneration and Redemption: Exploring Indian Philosophy in T.S Eliot’s ‘The Waste Land’ - Siddik, Md. Abu Bokkor (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
This study analyzes T.S Eliot's epoch-making poem ''The Waste Land'' to deeply investigate the crises of post-war modern European society manifested in the poem as spiritual degeneration, skepticism, adultery, temptation, mechanism, hypocrisy, anxiety and unfaithfulness. Qualitative method has been applied in the study to collect data and analyze them.The paper also explores the ways of salvation of the crises that are mentioned by the poet as giving, sympathizing and controlling. Moral crises occupy a great position in human civilization in the modern period where man has forgotten all his ethics, spiritual rebirth and even religion. It also examines how modern men and women lead their lives in life-in-death, how they follow their traditional routine and how modernism captures them. Again, the study brings out the moral degradation and its various aspects and argues that T.S Eliot is heavily influenced by Hinduism to find out the way of regeneration that is terribly important for the entire human race.Keywords: Sterility, Anxiety, Frustration, Mechanical Life, Hypocrisy, Salvation